Marketing in the sports industry: principles and tools - Krainia, V. P.; Poliakova, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
This article explores the process of marketing in the sports industry, its principles and tools for achieving success in this area, focusing on the interplay between athletes, media, sponsors, and spectators. It emphasizes how advertising, media rights sales, sponsorships, and other marketing techniques are applied to raise brand awareness and boost revenue.
Keywords: marketing; sports industry; advertising; promotion; management; marketing tools; principles